Analisis Efektivitas Penggunaan Alat Berat Crawler Crane pada Proyek Pembangunan Jalan Tol Jogja - Solo (Paket 1.2 Klaten – Purwomartani) - Mohammad Harun; Ahmad Suwandi; Alif Kamajaya (Institut Teknologi Adhi Tama Surabaya, 2025)
Toll road infrastructure development plays a vital role in increasing regional connectivity and logistics movement efficiency. One important element in bridge construction is heavy equipment such as a Crawler Crane, which is used to lift heavy structural components such as Pre-stressed Concrete I-Girders (PCI Girders). This study aims to analyze the effectiveness of Crawler Crane usage in the Jogja-Solo Toll Road construction project Package 1.2 (Klaten – Purwomartani), especially on the Klongkongan River Bridge segment STA 32+300 - 35+640. The research method used is descriptive quantitative with data collection through field observation of lifting cycles, interviews, and documentation study.The results show that the average installation cycle time for PCI Girders using the Crawler Crane is 70 minutes/girder, matching the planned duration. The Schedule Performance Index (SPI) value was 1.00, indicating that the work was completed on schedule. Operational cost savings reached 15.2% of the initially allocated Rp 525,000,000, reducing actual expenses to Rp 445,700,000. This reflects high cost efficiency, indicating that the planning and use of heavy equipment were optimal. The study also provides recommendations to further improve productivity, such as more efficient material rotation schedules and minimizing idle time.